Examining the effectiveness of BEE implementation: a case study of Eskom restructuring 1995-2005 - Shangase, G. Mabutho (My University, 2008)
Black Economic Empowerment (BEE) has emerged as the premier policy instrument to redress the socio-economic inequalities created by the apartheid system in South Africa. BEE has evolved from a rudimentary concept that was casually coined outside government in the 1990s to being the policy instrument du jour of the post 1994 democratic dispensation. BEE has received critical attention culminating in its institutionalization through a BEE Council, an Act of Parliament, and a policy framework to facilitate its implementation. The institutionalization of this concept across government policy and practice settings, including, in particular, the government’s drive to restructure its enterprises, has accentuated BEE’s important role in the government’s reconstruction and development agenda. However, the evolution of BEE has not been a smooth journey. Its capacity and direction to respond to dire socio-economic demands has raised a deluge of questions and remarks, often negative, from many fronts. The purpose of this study is to critically examine the extent to which BEE produces the targeted results through its implementation via the restructuring of state owned enterprises (SOEs). What is also of significance is that the restructuring of SOEs and the implementation of BEE is occurring against a backdrop of a conspicuous neo-liberal drive. Whilst setting the scene with a theoretical background to the South African economy before and after 1994, the practical focus of this study is limited to the implementation of BEE using Eskom, an SOE, as a case study. Just as this study indicates a successful implementation of BEE through Eskom, questions remain as to how much widespread the benefits have been amongst the targeted previously marginalized black majority.
Keywords: Black economic empowerment; Restructuring of state owned enterprises; Neo-liberalism; Eskom; Parastatals; Privatisation